A Simple Fragment of Cyclic Acyldepsipeptides Is Necessary and Sufficient for ClpP Activation and Antibacterial Activity. Issue 15 (11th September 2014) - Carney, Daniel W.; Compton, Corey L.; Schmitz, Karl R.; Stevens, Julia P.; Sauer, Robert T.; Sello, Jason K.
Abstract The development of new antibacterial agents, particularly those with unique biological targets, is essential to keep pace with the inevitable emergence of drug resistance in pathogenic bacteria. We identified the minimal structural component of the cyclic acyldepsipeptide (ADEP) antibiotics that exhibits antibacterial activity. We found that N‐acyldifluorophenylalanine fragments function via the same mechanism of action as ADEPs, as evidenced by the requirement of ClpP for the fragments' antibacterial activity, the ability of fragments to activate Bacillus subtilis ClpP in vitro, and the capacity of an N‐acyldifluorophenylalanine affinity matrix to capture ClpP from B. subtilis cell lysates. N‐acyldifluorophenylalanine fragments are much simpler in structure than the full ADEPs and are also highly amenable to structural diversification. Thus, the stage has been set for the development of non‐peptide activators of ClpP that can be used as antibacterial agents.